2018
DOI: 10.1002/jssc.201700832
|View full text |Cite
|
Sign up to set email alerts
|

Rapid preparation of methyltrimethoxy‐modified magnetic mesoporous silica as an effective solid‐phase extraction adsorbent

Abstract: A time-saving method was applied to synthesize methyltrimethoxy-modified magnetic mesoporous silica with or without p-toluenesulfonic acid as the catalyst for magnetic solid-phase extraction. The synthesized materials were systematically characterized. Results demonstrated that methyltrimethoxy modified magnetic mesoporous silica with p-toluenesulfonic acid as the catalyst has a relatively smaller aperture and extreme hydrophobicity (water contact angle of 135°). To evaluate the feasibility of these prepared m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…From the improved adsorption/recoveries of NDMA obtained through AC800, it is evident that hydrophobic interactions were dominant than hydrogen bonds. It was reported that hydrophobic interaction is an effective mechanism for the extraction of organic compounds [50]. The significant improvement in the recoveries achieved by AC800 indicated that heat treatment significantly favored the extraction of NDMA.…”
Section: Resultsmentioning
confidence: 99%
“…From the improved adsorption/recoveries of NDMA obtained through AC800, it is evident that hydrophobic interactions were dominant than hydrogen bonds. It was reported that hydrophobic interaction is an effective mechanism for the extraction of organic compounds [50]. The significant improvement in the recoveries achieved by AC800 indicated that heat treatment significantly favored the extraction of NDMA.…”
Section: Resultsmentioning
confidence: 99%
“…Magnetic nanoparticles were coated with the layer of mesoporous silica modified with methyl dimethoxy, and p-toluenesulfonic acid (PTSA) was used as a catalyst and finally, a will defined Fe3O4/mSiO2-Me-PTSA material was prepared (Qin et al, 2018a). The prepared Fe3O4/mSiO2-Me-PTSA material was used as MSPE sorbent for the efficient removal of polychlorinated biphenyls from wastewater samples.…”
Section: Magnetic Mesoporous Composites Materialsmentioning
confidence: 99%
“…Currently, several methods have been reported for the pretreatment of samples involving DS. Among them, solid-phase extraction has attracted remarkable attention due to its simple operation, low usage amount of organic solvent, and high recovery efficiency [10][11][12]. In this context, Soheili-Azad et al [13] reported a zinc/aluminum layered double hydroxide adsorbent (Zn/Al LDH) for the extraction and HPLC determination of trace DS from human serum and hospital wastewater.…”
Section: Introductionmentioning
confidence: 99%